Florid cemento-osseous dysplasia-related osteonecrosis: A series of cases - Bastos, Yann Victor Paiva; Carlos, Roman; Oliveira, Paulo Tambasco De; Pires, Bruno Cunha; Cangussu, Maria Cristina Teixeira; Xavier, Flávia Caló Aquino; Koga-Ito, Cristiane Yumi [UNESP]; Manieri, Patricia Rubia; Souza, André Sampaio; Júnior, Braúlio Carneiro; Ramalho, Luciana Maria Pedreira; Cury, Patrícia Ramos; et al. (Elsevier, 2022)
Objective: The aim of this study was to assess the clinicopathological features of florid cemento-osseous dysplasia (FCOD)-related osteonecrosis highlighting their histopathological aspects and bone structure. Methods: Twenty-two FCOD-related osteonecrosis cases were evaluated retrospectively. Osteonecrosis, osteomyelitis, bacterial colonization, bone resorption, reactive bone, osteon-like structure, lamellar bone, and basophilic lines were analyzed. Specific staining and fluorescence and polarized light microscopy analyses were also performed. Results: The mandible was more affected by FCOD-related osteonecrosis. There was a predominance of African-Brazilian women in the fifth and seventh decades of life. Osteomyelitis was present in 82 % of cases whereas bone resorption and bacterial colonization were present in 100 % of FCOD-related osteonecrosis cases. Thick basophilic lines were seen in all cases (100 %). Actinomycosis and osteoclasts were not often. Conclusions: This study showed female adult preference, mandibular location, and some findings such as osteomyelitis, bone resorption, and bacterial colonization were histopathological features more frequent in FCOD-related osteonecrosis. In the absence of a close clinical and radiographic correlation, the morphology of the necrotized bone similar to cementum could help to recognize FCOD.
Keywords: Cemento-osseous dysplasia; Mandible; Osteonecrosis